Developing an Editor for Drawing Class Diagram within WinCASE Framework - Klaib, Alhadi; Arbi, Abdelrahman; Ihnissi , Ragab (Journal of Pure & Applied Sciences, 2022)
Computer Aided Software Engineering (CASE) tools are significant for the software engineering field. They provide great support to software developers. WinCASE tool is one of these tools. It was invented in the Department of Computer Science at the University of Sheffield. Furthermore, dataflow Algebra is a methodology that is used to describe a formal specification of a system. Dataflow Algebra was also developed in the same department. Unified Modeling Language is a standard language for developing software systems. The class diagram is one of the UML diagrams which illustrates the system objects. This paper aims to upgrade the WinCASE tool by developing the Class diagram within the framework of this tool. Therefore, this paper reviewed the previous work and the background of the WinCASE framework, class diagram, Dataflow Algebra, the requirements of integrating the Class Diagram, and the methodology of this integration. Subsequently, the class diagram was implemented into the WinCASE framework; and then tested, and evaluated successfully as well. As a result, the WinCASE was provided with an editor for drawing the class diagram.